Haemothorax in the Context of HELLP Syndrome: Unravelling the Etiological Dilemma - A Rare Case Report (Journal of Forensic Medicine & Toxicology, 2025)
Background: Haemothorax denotes the pathological accumulation of blood in the pleural cavity, distinguished by the presence of  pleural fluid exhibiting a haematocrit that surpasses 50% of the peripheral haematocrit. Although predominantly associated with  traumatic origins, instances of spontaneous haemothorax are not without precedents. Spontaneous haemothorax encompasses a  multitude of causative factors and may manifest as a complication arising during pregnancy and parturition. Spontaneous haemothorax during pregnancy can arise from diverse factors, including diaphragmatic ectopic pregnancy, gestational trophoblastic disease,  peripartal hemoperitoneum, and rupture of subcapsular haematoma. However, it is noteworthy that, as per existing literature, hae mothorax secondary to HELLP syndrome characterised by “Haemolysis, Elevated Liver Enzymes, and Low Platelet counts” has not  been documented. Case Presentation: In this present case, a 34-year-old multiparous woman (gravida 3, para 2) was referred to  Vardhman Mahavir Medical College & Safdarjung Hospital, New Delhi, presenting with a full-term pregnancy. The patient reported  an alleged history of premature rupture of membranes and documented instances of self-induced falls, occurring on two separate  occasions, accompanied by a noted tongue bite. She received a clinical diagnosis of HELLP syndrome, leading to the imperative  intervention of an emergency lower (uterine) segment Caesarean section (LSCS), resulting in the delivery of a live baby. Tragically,  the patient succumbed the very next day. This case presentation highlights a clinically overlooked haemothorax, identified solely  during autopsy in a pregnancy-related fatality attributed to HELLP syndrome. The complicating factor was an antecedent trauma  before being admitted to the hospital. After meticulous examination, we have excluded the possibility of traumatic haemothorax,  instead attributing the gradual progression of haemothorax from the point of bleeding to be secondary to HELLP syndrome—an  unprecedented cause of mortality in the reported literature. Conclusions: The conclusion drawn, indicating that the clinical presentation with a gradual progression of haemothorax from the  bleeding point was secondary to HELLP syndrome, is supported by the evidence presented in the case. The recommendations for  attending clinicians to consider performing ultrasonographical tests in both thoracic and abdominal cavities for pregnant women  with HELLP Syndrome, particularly in the presence of low haemoglobin levels, is a valuable suggestion.
Keywords: HELLP Syndrome; Spontaneous; Haemothorax; Pregnancy-related deaths; Case Report.